A novel two-dimensional polyrotaxane network self-assembled by heterowheel [4]pseudorotaxane. Issue 3 (4th March 2017) - Zhou, Qiongbo; Li, Yaoji; Han, Zenghui; Gong, Li; Chen, Jinxin; Zhang, Hui; Xia, Jingyuan; Peng, Hua; Fang, Shixiang; He, Binbin; Yang, Wenquan; Liu, Lifen; et al.
Abstract: A novel heterowheel pseudorotaxane comprised of one guest, one cucurbit[7]uril and two cucurbit[6]urils was synthesised and characterised by 1 H NMR, single crystal X-ray diffraction analysis and thermogravimetric analysis. Single crystal X-ray diffraction analysis demonstrates that the heterowheel pseudorotaxane self-assembles into two-dimensional polyrotaxane network with the aid of water molecules and hydrogen bonds. Every four heterowheel pseudorotaxanes self-assemble into a parallelogram, which is the basic unit of the 2D network. Abstract : A novel heterowheel pseudorotaxane consisting of one guest, one cucurbit[7]uril and two cucurbit[6]urils was synthesised. Single crystal X-ray diffraction analysis demonstrates that the heterowheel pseudorotaxane self-assembles into two-dimensional polyrotaxane network with the aid of water molecules and hydrogen bonds. Every four heterowheel pseudorotaxanes self-assemble into a parallelogram, which is the basic unit of the 2D network.